Relationships between perceived coach leadership, athletes` use of coping and emotions among competitive table tennis players - González-Garcia, H.; Martinent, G. (European Journal of Sport Science, 2020)
The aims of this study were to examine: (a) whether coach leadership behaviours predict athletes` use of coping and (b) whether coping predicts athletes` emotional outcomes in competition. A sample of 180 table tennis players (Mage?=?33.87; SD = 16.64; 149 men and 31 women) voluntarily participated in the study. A partial least square path modelling (PLS-PM) approach was used to examine the relationships between the study variable. The results showed that: (a) coach democratic behaviour was significantly related to task-oriented coping; (b) task-oriented coping was significantly related to excitement and happiness; (c) distraction-oriented coping was significantly related to anxiety, dejection and anger. As a whole, PLS-PM results suggested that coach democratic behaviour could be the better style in relationship with positive coping and emotion outcomes in table tennis players.